Integrate Building Information Modeling (BIM) and Sustainable Design at the Conceptual Stage of Building Projects - Jalaei, Farzad (Université d'Ottawa / University of Ottawa, 2015)
Lately the construction industry has become more interested in designing and constructing environmentally friendly buildings (e.g. sustainable buildings) that can provide both high performance and monetary savings. Analyzing various parameters during sustainable design such as Life Cycle Assessment (LCA) and energy consumption, lighting simulation, green building rating system criteria and associated cost of building components at the conceptual design stage is very useful for designers needing to make decisions related to the selection of optimum design alternatives. Building Information Modeling (BIM) offers designers the ability to assess different design options and to select vital energy strategies and systems at the conceptual stage of proposed buildings. This thesis describes a methodology to implement sustainable design for proposed buildings at their conceptual stage. The proposed methodology is to be implemented through the design and development of a model that simplifies the process of designing sustainable buildings, evaluating their Environmental Impacts (EI), assessing their operational and embodied energy and listing their potential accumulated certification points in an integrated environment. Therefore, a Decision Support System (DSS) is developed by using Multiple Criteria Decision Making (MCDM) techniques to help design team decides and selects the best type of sustainable building components and design families for proposed projects based on three main criteria (i.e. Environmental, Economical factor «cost efficiency » and Social wellbeing) in an attempt to identify the influence of design variations on the sustainable performance of the whole building. The DSS outcomes are incorporated in an integrated model capable of guiding users when performing sustainable design for building projects. The proposed methodology contains five modules: 1) Database Management System (DBMS), 2) Energy and lighting analysis, 3) Life Cycle Assessment (LCA), 4) LEED and 5) Life Cycle Cost (LCC). To improve the workability of the proposed model, a use case of abovementioned modules are going to be created as plug-ins in BIM tool. The successful implementation of such a methodology represents a significant advancement in the ability to attain sustainable design of a building during the early stages, to evaluate its EI, and to list its potentially earned certification points and associated soft costs.
Keywords: Sustainable Design; Building Information Modeling (BIM); Life Cycle Assessment (LCA); Energy and lighting analysis; LEED; Life Cycle Cost (LCC); Green Buildings; Conceptual Stage